2007
DOI: 10.1016/j.learninstruc.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of negotiation of common ground in CSCL

Abstract: CSCL research has given rise to a plethora of analysis methods, all with specific analysis goals, units of analysis, and for specific types of data (chat, threaded discussions, etc.). This article describes some challenges of CSCL-analysis. The development of an analysis method for negotiation processes in multidisciplinary teams serves as an example of how these challenges occur in practice. Results reveal a number of tensions with regard to establishing reliable coding procedures without compromising validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 14 publications
0
50
1
4
Order By: Relevance
“…Recent research has identified a number of other task characteristics relevant Individual and Group-Based Learning 24 when considering group learning as a good option. This would, for example, be the case when positive cognitive conflict is necessary or desirable when solving a problem or creating a product, as is the case in argumentative learning (Munneke et al, 2007), when diversity in expertise or a multidisciplinary approach is necessary for carrying out a task or solving a problem (Kirschner et al, 2008), or when specific cognitive or metacognitive skills (e.g., reflection: King, 2007) or socio-cognitive skills (e.g., negotiation: Beers et al, 2007 or debating: Leitão, 2000;Veerman, Andriessen, & Kanselaar, 2000) are the required processes in and/or products of learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has identified a number of other task characteristics relevant Individual and Group-Based Learning 24 when considering group learning as a good option. This would, for example, be the case when positive cognitive conflict is necessary or desirable when solving a problem or creating a product, as is the case in argumentative learning (Munneke et al, 2007), when diversity in expertise or a multidisciplinary approach is necessary for carrying out a task or solving a problem (Kirschner et al, 2008), or when specific cognitive or metacognitive skills (e.g., reflection: King, 2007) or socio-cognitive skills (e.g., negotiation: Beers et al, 2007 or debating: Leitão, 2000;Veerman, Andriessen, & Kanselaar, 2000) are the required processes in and/or products of learning.…”
Section: Discussionmentioning
confidence: 99%
“…Activities such as self-directed learning, negotiating meaning (Beers, Boshuizen, & Kirschner, 2007;Kirschner, Beers, Boshuizen, & Gijselaers, 2008), verbalizing explanations, justifications and reflections, giving mutual support (Van Boxtel, Van der Linden, & Kanselaar, 2000), and developing arguments about complex problems or propositions (Munneke, Andriessen, Kanselaar, & Kirschner, 2007) have been found to facilitate the learning process. Collaborative learning has also been shown to help learners retain the learned information longer (Morgan, Whorton, & Gunsalus, 2000) and to foster their higher-order skills more than in more traditional lecture-based learning environments (Sloffer, Dueber, & Duffy, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in this so-called process-oriented tradition (Dillenbourg et al 1996; focus on interaction processes such as giving detailed, elaborated explanations (Webb and Farivar 1999), negotiating meaning (Beers et al 2007), co-constructing solutions and lines of reasoning (Van Boxtel et al 2000), and developing and formulating arguments during collaboration (Janssen et al 2010;Kuhn and Udell 2003).…”
Section: Process-oriented Collaborative Learning Research: Advantagesmentioning
confidence: 99%
“…Group-based learning is a good option when a multidisciplinary approach or diversity of expertise is needed to solve a problem or carry out a task (Kirschner, Beers, Boshuizen & Gijselaers, 2008). Other cases appropriate for group-based learning include argumentative learning (Munneke, Andriessen, Kanselaar & Kirschner, 2007) or when reflection (King, 2007), negotiation (Beers, Boshuizen & Kirschner, 2007) or debating are being taught (Leitão, 2000;Veerman, Andriessen & Kanselaar, 2000). Different groups of students can use different creative ways to solve the problems (Barrow, 2010).…”
Section: Pedagogical Rootsmentioning
confidence: 99%